Attractiveness of different sweet and fatty substances to three neotropical tramp ant species (Hymenoptera : Formicidae) - Solis, D. R. [UNESP]; Bueno, O. C. [UNESP]; Moretti, T. C. [UNESP] (California State University, 2008)
Urban ant pests were spread through the world mainly by commerce, infesting houses and hospitals. These ants are able to cause serious complications in hospitals, as they are capable of carrying pathogens. Specifically designed toxic baits have appeared in Brazilian markets in the last few years, and are currently replacing traditional ways for fighting off ant infestations. In the beginning, these baits were imported from temperate countries, but those proved inefficient. Nowadays, there are various different Brazilian ant baits, many of which have doubtful cfficiency. Studies of urban ants are recent in Brazil, and knowledge of their biology may aid in detecting weaknesses in their cycles that could be exploited in Integrated Pest Management programs. Thus, this study aimed at evaluating the attractiveness of sweet and fatty substances for the ant species Linepithema humile Mayr, Monomorium floricola Jerdon and Paratrechina longicornis Latreille, to select the most efficient ones to be used in baits. Each test was made with 10 colonies of each species, using 68 sweet substances and 23 fatty substances. Foods were presented to the ants in random sequence and position. The number of ants present over each food source was tracked every 10 min for 1 h. We determined ail attractiveness index for each food, used for statistical analysis of variance and comparison of means by Dunnett's test alpha = 0.05). The two most attractive substances of each type were then cross-tested together to verify if there was some preference by the ants for sweet or fatty foods. The tests revealed that 50% refined white sugar and unsalted margarine were the only substances attractive to all three ant species. When substances of both types were cross-tested, sweet substances proved more attractive than fatty ones.
Keywords: insecta; crazy ant; argentine ant; Linepithema humile; Monomorium floricola; Paratrechina longicornis